MARKET OPPORTUNITY TOWARD ONLINE SHOPPING IN BOOKSTORE BINA USAHA MEDAN - Daniel Cassa Augustinus; Carolin Onggo (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
Online shopping business method has been implemented by most businesses since the advancement of technology. Therefore, this research is conducted to recognize the market profile of Toko Buku Bina Usaha and to identify whether there is a market opportunity to implement online shopping on Toko Buku Bina Usaha or not. The methodology used in this research is quantitative inferential statistic method involving 132 respondents which are selected by convenience sampling method. The data collection methods of this research are interview, questionnaire, observation, IT interview and library research. Based on the finding, it can be concluded that there is market opportunity to apply online shopping method (online website) on Toko Buku Bina Usaha as part of its marketing strategy